2015
DOI: 10.1186/s12871-015-0036-6
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative smoking cessation counseling activities of anesthesiologists: a cross-sectional study

Abstract: BackgroundSmokers undergoing surgery are at a higher risk of complications than non-smokers. Preoperative evaluation by an anesthesiologist could provide an excellent opportunity to promote smoking cessation. Previous surveys of anesthesiologists have found that self-reported smoking cessation counseling rates have room for improvement, but no study has surveyed patients to obtain more accurate estimates.MethodsA single-center study was conducted from January 2010 to June 2010 in a tertiary teaching hospital. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…There is need for education of health care professionals and young physicians to promote smoking cessation before the operation in the in-patient management (24). There is strong evidence about the usefulness of the smoking cessation program given the reduction of smoking-related complications, and stopping tobacco usage needs to be a part of preoperative rehabilitation (24). Smoking cessation training should be included in the education of medical students and prevention guidelines (19).…”
Section: Smokingmentioning
confidence: 99%
“…There is need for education of health care professionals and young physicians to promote smoking cessation before the operation in the in-patient management (24). There is strong evidence about the usefulness of the smoking cessation program given the reduction of smoking-related complications, and stopping tobacco usage needs to be a part of preoperative rehabilitation (24). Smoking cessation training should be included in the education of medical students and prevention guidelines (19).…”
Section: Smokingmentioning
confidence: 99%
“…For example, the majority of elective assessments occurred on the day of surgery when time barriers may have been a factor preventing anaesthetists engaging with tobacco discussions. It is possible that higher levels of preoperative smoking cessation counselling could occur in a preoperative clinic setting that takes place some days or weeks before surgery 12 when the clinical environment may be better for patients and anaesthetists for such discussions.…”
Section: Discussionmentioning
confidence: 99%
“…recorded anesthesiologist-delivered interventions to help quit smoking before surgery. [ 15 ] Studies showed intensive smoking and alcohol cessation intervention 6–8 weeks before elective surgery could reduce postoperative morbidity by about 50%. [ 16 ] Postoperative smoking-cessation in elective surgery and after fractured surgery might likewise reduce complications.…”
Section: Preoperative Cessation Of Smoking Drinking and Recreationamentioning
confidence: 99%